Allelopathic potentialities of extracts of leaf litter of some selected tree species on wheat in field condition - Banga, Akshita; Bana, O.P.S.; Yadava, Anil; Sah, V.K.; Chaturvedi, Sumit; ., Jyoti; Tripathi, P.; Bisht, N. (Indian Journal of Agroforestry, 2020)
Allelopatic effect of aqueous leaf extract of four agroforestry tree species viz., Populus deltoides, Eucalyptus hybrid, Anthocephalus cadamba, Terminalia chebula were examined on growth and yield of wheat in the Tarai region of Uttarakhand. The experiment was conducted in pot with thirteen treatments i.e. rhizospheric soil collected from underneath various tree species (i.e. Poplar, Eucalypt, Kadam, Harar) irrigated either with leaf extract of corresponding species or with normal water and normal soil collected from open field irrigated with either tree leaf extracts or normal water (control). The leaf extracts at 2 % concentration were applied only for first irrigation and later irrigations with normal water. The growth and yield of wheat was favoured by rhizospheric soil irrigated with corresponding tree leaf extract over either rhizospheric soil with normal water or normal soil plus leaf extracts/ water. The maximum grain yield of 13.03 (g/pot) was recorded with ES2L2 (rhizospheric soil from underneath Eucalypt irrigated with leaf extract of Eucalpyt, which was at par with ES1L1 (enriched soil from Poplar with Poplar extract), ES3L3 (enriched soil from Kadam with Kadam extract), ES3NW (enriched soil from Kadam with normal water) and ES4L4 (enriched soil from Harar with Harar extract).